2016
DOI: 10.1016/j.jcin.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and Antiplatelet Therapy Versus Warfarin Alone for Treating Patients With Atrial Fibrillation Undergoing Transcatheter Aortic Valve Replacement

Abstract: In TAVR recipients prescribed VKA therapy for AF, concomitant antiplatelet therapy use appears not to reduce the incidence of stroke, major adverse cardiovascular events, or death, while increasing the risk of major or life-threatening bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…A decision was made to switch from dual antiplatelet therapy (DAPT) without a loading dose prior to TAVR to single antiplatelet therapy (SAPT) with a P2Y 12 loading dose prior to TAVR for patients who do not require chronic systemic anticoagulation. This change in protocol was based on data from small trials and meta‐analyses that demonstrated similar efficacy and improved safety profile with SAPT versus DAPT . Patients requiring anticoagulation were treated with anticoagulation alone (no antiplatelet drugs) before or after TAVR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decision was made to switch from dual antiplatelet therapy (DAPT) without a loading dose prior to TAVR to single antiplatelet therapy (SAPT) with a P2Y 12 loading dose prior to TAVR for patients who do not require chronic systemic anticoagulation. This change in protocol was based on data from small trials and meta‐analyses that demonstrated similar efficacy and improved safety profile with SAPT versus DAPT . Patients requiring anticoagulation were treated with anticoagulation alone (no antiplatelet drugs) before or after TAVR.…”
Section: Methodsmentioning
confidence: 99%
“…Patients requiring anticoagulation were treated with anticoagulation alone (no antiplatelet drugs) before or after TAVR. Anticoagulation was held 2 days prior to the procedure and restarted on the day after the procedure without bridging therapy . Chart review of all patients who underwent TAVR during the 9‐month study period identified 266 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of APT to VKA in patients with TAVI is associated with similar stroke or death rates, but an increased rate of major and/or life-threatening bleeding 29. In another study, VKA monotherapy resulted in a lower risk of the combined endpoint of post-procedural mortality, stroke, embolism and major bleeding 30…”
Section: Oral Anticoagulationmentioning
confidence: 99%
“…Patients with valve thrombosis or atrial fibrillation may need anticoagulation with VKA therapy. Abdul-Jawad et al[39] revealed that for patients with VKA therapy, concomitant antiplatelet therapy had no significant difference on stroke or death, while significantly increasing the incidence of major and lethal bleeding. However, the clinical outcomes remain unclear.…”
Section: Discussionmentioning
confidence: 99%